Le discernement ignatien et l'invention de la Compagnie de Jésus - Demoustier, Adrien (Gregorianum, 2004)
It was only progressively, by confronting their spiritual experience and the cultural conditions of their apostolate, that Ignatius and his companions were led to found a new order and then to recognize the importance of teaching in colleges. This article sets out the different stages of that progressive discovery. It recalls how Ignatius passed from his chivalrous desires to those of service of and in the Church, by attending to the interior experience of the Spiritual Exercises and to their being set down in writing. The experience of liberty and an objectifying putting down in writing were two poles, characteristic of modernity, that formed the main bases for inventing Jesuit colleges. Moreover, they were also bases which supported the writing of the Constitutions of the Society. For the Jesuits of today they remain ever innovative points of reference for discernment.